2014
DOI: 10.1016/j.scitotenv.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to reduce exposure to fungi, β-glucan, bacteria, endotoxin and dust in vegetable greenhouses and a packaging unit

Abstract: Indoor handling of large amounts of plant materials occurs in different occupational settings including greenhouses and causes exposure to bioaerosols. The bioaerosol components fungi, β-glucan, bacteria and endotoxin are involved in different airway symptoms and health effects can be dose-dependent. Therefore, there is a persistent need to reduce exposure. The aims of this study were to identify tasks causing exposure and to evaluate preventive measures aimed at reducing exposure of greenhouse workers to bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…However, we found that the fungal concentrations in the personal samples were consistently higher than those in the area samples, although the difference was not significant, probably because of a small sample size. Similar results were observed in a Danish study conducted in vegetable greenhouses (Madsen et al, 2014). Because workers often disturbed bioaerosol sources during activities, such as mixing material, picking vegetables, digging soil, and packaging, thus increasing the personal exposure concentrations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, we found that the fungal concentrations in the personal samples were consistently higher than those in the area samples, although the difference was not significant, probably because of a small sample size. Similar results were observed in a Danish study conducted in vegetable greenhouses (Madsen et al, 2014). Because workers often disturbed bioaerosol sources during activities, such as mixing material, picking vegetables, digging soil, and packaging, thus increasing the personal exposure concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Various studies have evaluated bioaerosol exposure on agricultural farms (Chang et al, 2002;Lee et al, 2006;Matkovic et al, 2009;Madsen, 2011;Hansen et al, 2012;Lee and Liao, 2014;Madsen et al, 2014;Viegas et al, 2014;Chow et al, 2015); of these, only a few have been conducted in Taiwan (Chang et al, 2002;Lee and Liao, 2014). In addition, studies focusing on the health risks of occupational fungal exposure on farms are scant (Yoshikawa et al, 2007;Adhikari et al, 2011;Ampere et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that cleaning the aisles after leaf nipping resulted in a significantly higher exposure to endotoxin (Madsen et al, 2014). In this study, days when a sweep was performed did not always reflect an increase in the concentrations of Oidium or Torula spores (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…In greenhouses, the growth conditions for plants are optimized to increase crop yields (Hansen et al, 2010). However, indoor handling of large amounts of plant materials occurs in different occupational settings, including greenhouses, and causes exposure to bioaerosols (Madsen et al, 2014). As indoor air is highly dynamic, studies have been carried out to examine indoor air quality, especially for occupational and public health purposes (Bonetta et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation